The Prevalence of Double Eyelid and the 3D Measurement of Orbital Soft Tissue in Malays and Chinese - Lu, T.Y.; Kadir, K.; Ngeow, Wei Cheong; Othman, Siti Adibah (Nature Publishing Group, 2017)
This study aimed to determine the prevalence of double eyelid among two main Mongoloid ethnicities, the Malays and Chinese who reside in Malaysia. We also measured their periorbital tissue parameters for application in anthropology, optometry, ophthalmology, oculoplastic surgery and maxillofacial trauma surgery. The images of the 103 Malay and 97 Chinese volunteers were captured using indirect 3D photogrammetry, and quantitative measurement was obtained using the software provided by the manufacturer. All Malays and 70.1% of Chinese in this cross section population had double eyelid on both eyes. The mean pretarsal skin height was 3.99 mm for the Malays and 2.29 mm for the Chinese. The Malays appeared to have shorter eyebrow height (11.10 mm) compared to the Chinese (11.79 mm). An opposite pattern could be seen in the measurement of upper eyelid crease height between the Malays (8.33 mm) and the Chinese (4.91 mm). Of note, the intercanthal distance of the Chinese (IDC = 35.85 mm) was wider and their interpupillary distance was narrower (IPD = 62.85 mm) compared to the Malays' (ICD = 34.21 mm; IPD = 64.04 mm). In conclusion, there were significant differences in the prevalence of double eyelid and periorbital tissue measurements between the Malays and Chinese.